Cancer mortality by country of birth and cancer type in Sweden: A 25‐year registry‐based cohort study - Daniel Nigusse Tollosa; Kazem Zendehdel; Alessandro Procopio; Agneta Cederström; Paolo Boffetta; Eero Pukkala; Mikael Rostila (Cancer Medicine)
Abstract Numerous studies have reported lower overall cancer mortality rates among immigrants compared to native populations. However, limited information exists regarding cancer mortality among immigrants based on specific birth countries and cancer types. We used population‐based registries and followed 10 million individuals aged 20 years or older in Sweden between 1992 and 2016. The Cox proportional hazard model was used to explore the disparities in cancer mortality by country of birth and cancer type, stratified by gender. Age‐standardized mortality rates were also computed using the world standard population. Hazard ratio (HR) of all‐site cancer was slightly lower among immigrants (males: HRm = 0.97: 95% confidence interval: 0.95, 0.98; females: HRf = 0.93: 0.91, 0.94) than Swedish‐born population. However, the immigrants showed higher mortality for infection‐related cancers, including liver (HRf = 1.10: 1.01, 1.19; HRm = 1.10: 1.02, 1.17), stomach (HRf = 1.39: 1.31, 1.49; HRm = 1.33: 1.26, 1.41) cancers, and tobacco‐related cancers, including lung (HRm = 1.44: 1.40, 1.49), and laryngeal cancers (HRm = 1.47: 1.24, 1.75). The HR of mesothelioma was also significantly higher in immigrants (HRf = 1.44: 1.10, 1.90). Mortality from lung cancer was specifically higher in men from Nordic (HRm = 1.41: 1.27, 1.55) and non‐Nordic Europe (HRm = 1.49: 1.43, 1.55) countries and lower in Asian (HRm = 0.78: 0.66, 0.93) and South American men (HRm = 0.70: 0.57, 0.87). In conclusion, there are large variations in cancer mortality by country of birth, and cancer type and require regular surveillance. Our detailed analyses lead to some novel findings such as excess mortality rate of mesothelioma and laryngeal cancers in Immigrants in Sweden. A targeted cancer prevention program among immigrants in Sweden is needed.